Analisis Persepsi Kualitas Produk, Kualitas Pelayanan Dan Word Of Mouth Terhadap Keputusan Pembelian Di UKM. Budi Utama Denpasar - Moh Gilang Prasetyo; I Wayan Sunia; Ni Putu Nina Eka Lestari (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study highlights the complexity of determining factors in the purchasing decision-making process among SMEs, with a specific focus on Budi Utama Denpasar SMEs. The analytical framework developed integrates three main constructs: Product Quality Perception as a representation of intrinsic attributes, Service Quality as an interactional dimension, and Word of Mouth as a social influence mechanism. The research design applied a quantitative approach through a survey of 71 respondents from a total population of 704 consumers. The data collection method combined a standardized questionnaire with supporting document analysis. The analytical process was conducted comprehensively using SPSS 26, including verification of classical assumptions, construction of a multiple linear regression model, and evaluation of statistical significance through t-tests and F-tests. The results of the analysis prove the positive and significant influence of the three independent variables, with the highest coefficient in Service Quality (β=0.532; t=7.222; p<0.001), followed by Word of Mouth (β=0.348; t=4.258; p<0.001), and Product Quality Perception (β=0.261; t=3.397; p<0.01). The overall validity of the model was confirmed by a calculated F value of 31.545 (p<0.001). These findings underscore the urgency of a holistic approach to SME marketing management that combines product excellence, service quality, and word-of-mouth communication strategies.